Gain Improvement in Two-stage L-Band EDFA with Incorporation of Fiber Bragg Grating - Harun, Sulaiman Wadi (De Gruyter, 2005)
The gain improvement in two-stage long wavelength band erbium doped fiber amplifier (L-band EDFA) is demonstrated by incorporation of broadband C-band fiber Bragg grating (FBG). The FBG is used to reflect the unwanted backward C-band ASE from second stage back into the system. The proposed technique has improved the small signal gain from 19.6 dB to 23.5 dB compared to those of an amplifier without the FBG. Besides gain improvement, this technique also reduces noise figure and the maximum noise figure improvement of 1.8 dB was obtained at input signal power of 0 dBm. At wavelength range from 1570 to 1600 nm, the gain of the proposed amplifier varies from 20.0 to 28.5 dB. The flat-gain is expected to be obtained by optimization of EDF length and pump powers. The corresponding noise figures are varied from 4.8 to 5.2 dB.